Vacuolar nicotianamine has critical and distinct roles under iron deficiency and for zinc sequestration in Arabidopsis - Haydon, Mike; Wirtz, Markus; Hillmer, Stefan; Hell, Rüdiger (The plant cell, 2012)
The essential micronutrients Fe and Zn often limit plant growth but are toxic in excess. Arabidopsis thaliana ZINC-INDUCED FACILITATOR1 (ZIF1) is a vacuolar membrane major facilitator superfamily protein required for basal Zn tolerance. Here, we show that overexpression of ZIF1 enhances the partitioning into vacuoles of the low molecular mass metal chelator nicotianamine and leads to pronounced nicotianamine accumulation in roots, accompanied by vacuolar buildup of Zn. Heterologous ZIF1 protein localizes to vacuolar membranes and enhances nicotianamine contents of yeast cells engineered to synthesize nicotianamine, without complementing a Zn-hypersensitive mutant that additionally lacks vacuolar membrane Zn2+/H+ antiport activity. Retention in roots of Zn, but not of Fe, is enhanced in ZIF1 overexpressors at the expense of the shoots. Furthermore, these lines exhibit impaired intercellular Fe movement in leaves and constitutive Fe deficiency symptoms, thus phenocopying nicotianamine biosynthesis mutants. Hence, perturbing the subcellular distribution of the chelator nicotianamine has profound, yet distinct, effects on Zn and Fe with respect to their subcellular and interorgan partitioning. The zif1 mutant is also hypersensitive to Fe deficiency, even in media lacking added Zn. Therefore, accurate levels of ZIF1 expression are critical for both Zn and Fe homeostasis. This will help to advance the biofortification of crops.